Native and Edible Ornamental Plant Congeners Enhance Ecosystem Services Through Key Pest Avoidance and Multifunctionality in Residential Landscapes. Issue 5 (29th August 2020) - Borden, Matthew A; Dale, Adam G
Abstract: Tea scale, Fiorinia theae Green (Hemiptera: Diaspididae), has long been one of the most important pests of Ilex and Camellia plants, particularly in the southeastern United States. This exotic armored scale insect reduces host plant health and function, and often requires insecticide use, which poses risks to nontarget organisms. While the use of Ilex (Aquifoliales: Aquifoliaceae) and Camellia (Ericales: Theaceae) spp. as landscape ornamentals for aesthetic function is firmly established, we have a poor understanding of species-level susceptibility to F. theae . Additionally, two species, Ilex vomitoria Ait. and Camellia sinensis (L.) O. Kuntze are emerging tisane- and tea-producing commodities in the region, respectively. We propose that these consumable plants may be well-suited alternatives to their traditionally used ornamental congeners in residential landscapes where they may provide enhanced ecosystem services. However, the potential impact of key pests, like F. theae, on these species should be evaluated to anticipate pest pressure that may undermine or offset benefits. In this study, we examine six species within the known host range of tea scale, comparing nonnative I. cornuta Lindl. 'Dwarf Burford, ' C. japonica L., C. sasanqua Thunb., and C. sinensis, along with native I. opaca Ait. and I. vomitoria . We found that plant species show a wide range of susceptibility to F. theae and associated damage, with the two native Ilex species and tea-producing C. sinensis displaying the least susceptibility. By reducing the impact of a key pest and considering other ecosystem service traits, these results may help guide more sustainable plant selection decisions where the goal is to integrate native and edible plants into residential landscapes.